2007
DOI: 10.1111/j.1365-3059.2006.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial nucleotide sequence analysis of Turkish isolates of Beet necrotic yellow vein virus (BNYVV) RNA‐3

Abstract: A survey was carried out to detect Beet necrotic yellow vein virus (BNYVV) in soil samples using RT-PCR and bait plant techniques from the sugar beet production area of Tokat, Turkey in 2001. More than 80% of the soil samples analyzed were found to be contaminated with the virus. The partial nucleotide sequence of cDNA corresponding to RNA-3 of BNYVV isolates were analyzed for six different regions of Tokat province. All isolates were assigned to type A strains based on RFLP analysis and DNA sequences. Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…the A, B and P types, have highly conserved genomes. Nucleotides 199-210 of the P25-coding region, however, show considerable sequence variation, especially in A type BNYVV (Tamada et al, 2003;Meunier et al, 2003;Schirmer et al, 2005;Ward et al, 2007;Kutluk Yilmaz et al, 2007;Li et al, 2008;Koenig et al, 2008). This stretch of nucleotides codes for the P25 aa 67-70, which in the following will be referred to as the 'tetrad'.…”
mentioning
confidence: 99%
“…the A, B and P types, have highly conserved genomes. Nucleotides 199-210 of the P25-coding region, however, show considerable sequence variation, especially in A type BNYVV (Tamada et al, 2003;Meunier et al, 2003;Schirmer et al, 2005;Ward et al, 2007;Kutluk Yilmaz et al, 2007;Li et al, 2008;Koenig et al, 2008). This stretch of nucleotides codes for the P25 aa 67-70, which in the following will be referred to as the 'tetrad'.…”
mentioning
confidence: 99%
“…Previous nucleotide analyses of RNA-3 and RNA-5 of Turkish isolates assigned these species as A-type and East Asian J-type 39,43 respectively. RFLP-based analyses of the isolates from the northern and central parts of Turkey designated RNA-2 and RNA-3 as A-type species 42,43 nevertheless, RFLP results of some isolates did not match the expected band profile which was the www.nature.com/scientificreports www.nature.com/scientificreports/ inspiration for the current study to examine the presence of polymorphism among Turkish isolates. RNA-1-5 analyses of BNYVV isolated from different regions of Thrace and Anatolia (modern-day Turkey) revealed a unique polymorphism which could be the probable causes of the failure of RFLP analysis in the previous study 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the first record of BNYVV infection in Turkey 40 several research works have diagnosed the disease in sugar beet fields of the country; however, only a few studies have partially characterized the virus 39,41-43 . Partial sequence analyses of RNA-3 isolated from Tokat province in the mid Black Sea region of Anatolia described www.nature.com/scientificreports www.nature.com/scientificreports/ some differences in the amino acid sequence of the Turkish isolates 43 . Previous nucleotide analyses of RNA-3 and RNA-5 of Turkish isolates assigned these species as A-type and East Asian J-type 39,43 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our BNYVV isolates were not digested by these restriction enzymes, suggesting that the isolate from R. raphanistrum belongs to the A type strain (Figure 3). The A type, the most widespread strain (Schirmer et al, 2005), has been previously detected in Turkey (Kruse et al, 1994;Kutluk Yilmaz et al, 2007); the B type strain is more restricted and mainly found in Germany, France (Kruse et al, 1994;Koenig et al, 2008), Japan (Miyanishi et al, 1999), and China (Li et al, 2008).…”
Section: Detection Of Bnyvvmentioning
confidence: 99%